Neutrophil to Lymphocyte Ratio Predicts Adverse Cardiovascular Outcome in Peritoneal Dialysis Patients Younger than 60 Years Old. (20th May 2020) - Zeng, Yingsi; Chen, Zijun; Chen, Qinkai; Zhan, Xiaojiang; Long, Haibo; Peng, Fenfen; Zhang, Fengping; Feng, Xiaoran; Zhou, Qian; Liu, Lingling; Peng, Xuan; Evergreen Tree Nephrology Association,; et al.
Abstract : Background . Neutrophil to lymphocyte ratio (NLR) is a new inflammatory marker; the relationship between NLR and adverse cardiovascular (CV) prognosis has been gradually emphasized in the general population. However, their association in peritoneal dialysis (PD) patients remains unclear. Methods . From January 1, 2010, to May 31, 2017, a total of 1652 patients were recruited. NLR was categorized in triplicates: NLR ≤ 2.74, 2.74 < NLR ≤ 3.96, and NLR > 3.96 . Kaplan-Meier cumulative incidence curve and multivariable COX regression analysis were used to determine the relationship between NLR and the incidence of adverse CV outcome, while a competitive risk model was applied to assess the effects of other outcomes on adverse CV prognosis. Besides, forest plot was investigated to analyze the adverse CV prognosis in different subgroups. Results . During follow-up, 213 new-onset CV events and 153 CV disease (CVD) deaths were recorded. Multivariable COX regression models showed that the highest tertile of NLR level was associated with increased risk of CV events (HR = 1.39, 95 % CI = 1.01 ‐ 1.93, P = 0.046 ) and CVD mortality (HR = 1.81, 95 % CI = 1.22 ‐ 2.69, P = 0.003 ), while compared to the lowest tertile. Competitive risk models showed that the differences in CV event (P < 0.001 ) and CVD mortality (P = 0.004 ) among different NLR groups were still significant while excluding the effects of other outcomes. In subgroups, with each 1 increased in the NLR level, adjusted HR of new-onset CV event was 2.02 (95 % CI = 1.26 − 3.23, P = 0.003 ) and CVD mortality was 2.98 (95 % CI = 1.58 − 5.62, P = 0.001 ) in the younger group (age < 60 years). Conclusions . NLR is an independent risk factor for adverse CV prognosis in PD patients younger than 60 years old.